Sistem Pendukung Keputusan Pemilihan Produk Whey Protein Terbaik Dengan Menggunakan Metode Smarter - denta Mustofa (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2022)
Whey protein is considered important as a supplement to help meet nutrition, but the many types and products of whey protein make it difficult for novice gym users to choose products that suit their needs. This study aims to build a Decision Support System (DSS) to choose the right whey protein product. In this research, the Simple Multi Attribute Rating Technique Exploiting Rank (SMARTER) method is implemented to calculate the weight of the criteria and sub-criteria with the ROC formula, then calculate the utility and calculate the final value to then produce the recommended whey product ranking. the criteria used are cosh, calories, cholesterol, sodium, carbohydrates, sugar, and protein. Tests in this study using the Technology Acceptance Model (TAM) on the usefulness aspect showed a result of 0.931 which means that the Decision Support System (DSS) that was built was considered very useful by users.